PEMBUATAN MODUL FISIKA BERBASIS TIK UNTUK MENGINTEGRASIKAN NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SISWA SMAN 10 PADANG KELAS X SEMESTER 1 - Yopy Mardiansyah (Universitas Negeri Padang, 2013)
The purpose of learning process is to create the intellectual and to develop the characters of students. The integration of characters value in learning process is important. One solution to overcome the problem is to develop an module based on ICT to integrate the character values. The general purpose of this research is to produce a module based on ICT to integrate the character valid that valid, practice, and effective to use in learning process. The type of this research is Research and Development (R & D). It uses before-after experimental design. Object of this research is module based on ICT. Subjects of this research are 31 students of X.5 at SMA 10 Padang. The instruments are used to collect the data in this research are: validity sheet, practicality sheet, learning outcomes test sheet, and questionary sheet. Based on analyze of the data, There are four result of this research. First, module has high validation score 87. Second, the design of this module has menu home, competence, learning evaluation, and download which are completed by video and animation as well as are packaged in CD. Third, the value of practicality of module according to the teachers and students are 85,46 and 87,60. Fourth, this module effectives to increase learning outcomes and develops the character value of the students. Keywords— Module, ICT, Characters value, Validity, Practicality, effectivity